Dipterological surveys in Portugal unveil 200 species of long-legged flies, with over 170 new to the country (Diptera: Dolichopodidae) - Pollet, Marc; Andrade, Rui; Gonçalves, Ana; Andrade, Pedro; Jacinto, Valter; Almeida, Jorge; de Braekeleer, Anja; van Calster, Hans; Brosens, Dimitri (Zootaxa, 2019)
A first comprehensive account on the dolichopodid fauna (Diptera: Dolichopodidae) of Portugal is presented as the result of multiple surveys by primarily Portuguese researchers between 2009 and 2016. All mainland Portuguese provinces and all districts but one (Évora) were investigated. A total of 761 dolichopodid samples were collected in 278 sampling sites distributed over 87 municipalities and 182 localities, with nearly ¾ of the samples gathered by sweep net. They contained 6,680 specimens of 200 different species, with 142 recognized (known), 40 new (undescribed) and 18 doubtful species. Medetera and Dolichopus were the most diverse among the recognized species, with 20 and 18 species respectively. Fourteen genera were represented by the new species, with Medetera as most diverse. The doubtful species included one species of Pelastoneurus, which is a first record of this genus for the Palaearctic realm. At present 208 dolichopodid species are known from Portugal. A checklist with 150 recognized species is presented, with first records of 116 species for Portugal. For nearly every species, information on its distribution, ecology and rarity in Portugal and northwestern Europe is given, as well as its seasonal activity in Portugal. Raw distribution data are available as dataset in GBIF. Seventy-five pictures of species in the field, and 15 habitat photos are also provided. Current data suggest that a higher proportion of Portuguese species are rare as compared to the Flemish fauna (northern Belgium). Both share 104 species, with 38 species only recorded from Portugal; only seven can be considered Iberian or Portuguese specialities. Though differences between the two Portuguese biomes cannot be substantiated at this moment, two very common and widespread European species, Campsicnemus scambus and Chrysotimus molliculus, seem to be restricted to the Eurosiberian biome in the northwest of the country. In terms of generic representation, the Portuguese dolichopodid fauna occupies an intermediate position between those of northwestern European and other Mediterranean countries. Despite the large amount of data gathered, the dolichopodid fauna of Portugal remains insufficiently known and a considerable number of additional known and new species can be expected with continued sampling.